Determination and quantification of ethanol and byproducts using HPLC (Brand: WATERS) - Azmi, Azlin Suhaida (IIUM Press, 2016)
Ethanol has extensive applications especially as a solvent and a feedstock for synthesis of other products. It also has other uses such as for consumption (including scents and flavourings), colourings, medicines, personal care products, cleaning products, and can be served as solvent in perfume, aerosols, paint, lacquer and explosive (O'Leary, 2000). On top of that, ethanol is also used as an alternative fuel which is usually blended with gasoline and is used in unmodified car engine. Non-petroleum-based ethanol is produced from biological sources such as sugar, starch or cellulose. Depend on which type of the sources, the conversion steps varies and produce byproducts. For an example, the conversion of polysaccharide starch into ethanol which is an indirect fermentation normally takes three separate steps. The first step is liquefaction using -amylase enzyme, which reduces the viscosity of the starch and fragments the starch into regularly sized chains, to yield dextrin, maltose, maltotriose and maltopentose followed by saccharification, whereby the starch is converted into sugar using glucoamylase enzyme. The final step involves the fermentation of sugar into ethanol using yeast. Depend on type of microorganisms; the fermentation will yield several other byproducts such as glycerol, lactic acid and acetic acid. The soluble sugar can be detected and quantified using HPLC with refractive index detection (Sluiter, Hames, Ruiz, Scarlata, Sluiter, & Templeton, 2008). Column such as IC-Pak Ion Exclusion with pre-column (SH-1011P) connected to HPLC system can capture most of these byproducts together with ethanol in a short time.